Student Independent Training at the Merdeka Campus Study at the Merdeka Campus: Pelatihan Mandiri Mahasiswa Pada Kampus Merdeka Belajar Kampus Merdeka - Lesi Hertati; Asmawati Asharie; Lili Syafitri (Universitas Lancang Kuning, 2023)
This service examines the role of students in Merdeka Learning Kampus Merdeka (MBKM) activities in order to create creativity, innovation, superior information technology in creating competitive advantage and new learning patterns in exchange of campus learning with a new atmosphere. The government's policy of creating MBKM encourages students to develop themselves, new ideas, a new atmosphere can form a new academic atmosphere as well as knowledge and skills that can motivate students to learn and share knowledge to enrich knowledge and creative ideas. This dedication activity was taken from 300 students who were active in the Indo Global Mandiri University accounting study program. The results of community service activities show that students who take part in the MBKM program can provide considerable benefits such as competence, comprehension, innovation challenges, soft skills and hard skills, skills using competent hardware and software. Students are expected to be able to create new ideas in broader socialization of MBKM such as apprenticeships at companies and exchange of learning between campuses that already have an MOU